2023
DOI: 10.3389/fmicb.2023.1141585
|View full text |Cite
|
Sign up to set email alerts
|

Diseased-induced multifaceted variations in community assembly and functions of plant-associated microbiomes

Abstract: Plant-associated microorganisms are believed to be part of the so-called extended plant phenotypes, affecting plant growth and health. Understanding how plant-associated microorganisms respond to pathogen invasion is crucial to controlling plant diseases through microbiome manipulation. In this study, healthy and diseased (bacterial wilt disease, BWD) tomato (Solanum lycopersicum L.) plants were harvested, and variations in the rhizosphere and root endosphere microbial communities were subsequently investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Studies have revealed the characteristics of suppressive soils, specifically the underlying mechanism of “take-all decline” ( Cook et al., 1995 ); and they discovered the disease decline is the result of systemic acquired resistance gained through defensive microbe recruitment ( Liu et al., 2021 ). The phenomenon has not been considered from this paradigm in the beginning; however, current studies have indicated pathogen-induced microbiome recruitment and its remarkable effect on defensive microbiome assembly ( Carrión et al., 2019 ; Kuang et al., 2023 ). The recruited microbes will induce systematic resistance in plants, while they may also directly confront pathogens in the system ( Figure 1 ) through the secretion of secondary metabolites or competition for nutrients and space ( Getzke et al., 2023 ).…”
Section: Factors Determining Pathogen Suppressive Microbiome Assemblymentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have revealed the characteristics of suppressive soils, specifically the underlying mechanism of “take-all decline” ( Cook et al., 1995 ); and they discovered the disease decline is the result of systemic acquired resistance gained through defensive microbe recruitment ( Liu et al., 2021 ). The phenomenon has not been considered from this paradigm in the beginning; however, current studies have indicated pathogen-induced microbiome recruitment and its remarkable effect on defensive microbiome assembly ( Carrión et al., 2019 ; Kuang et al., 2023 ). The recruited microbes will induce systematic resistance in plants, while they may also directly confront pathogens in the system ( Figure 1 ) through the secretion of secondary metabolites or competition for nutrients and space ( Getzke et al., 2023 ).…”
Section: Factors Determining Pathogen Suppressive Microbiome Assemblymentioning
confidence: 99%
“…The rhizosphere is generally colonized by various microbes and the microbiome composition differs greatly between diseased and healthy plants ( Kuang et al., 2023 ). This implies that pathogens can be used to shape the microbiome structure in the rhizosphere.…”
Section: Emerging Strategies For Shaping Rhizosphere Microbiomementioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have focused on comparing the differences in soil microbial communities between diseased and healthy plants ( Liang et al, 2021 ; Hossain et al, 2022 ; Tang et al, 2023 ). However, there is still limited research on the response mechanism of soil bacterial communities and plants to the pathogen attack ( Lu et al, 2022 ; Kuang et al, 2023 ). In this study, we explored the succession of soil bacterial communities of the healthy and diseased plants after N. benthamiana inoculated with TMV to indicate the role of soil bacterial communities in controlling TMV and the potential beneficial microbes.…”
Section: Introductionmentioning
confidence: 99%